2019
DOI: 10.1002/chem.201805693
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of the Novel Growth Inhibitor Streptol Glucoside, Isolated from an Obligate Plant Symbiont

Abstract: The plant Psychotria kirkii hosts an obligatory bacterial symbiont, Candidatus Burkholderia kirkii, in nodules on their leaves. Recently, a glucosylated derivative of (+)-streptol, (+)-streptol glucoside, was isolated from the nodulated leaves and was found to possess a plant growth inhibitory activity. To establish a structure-activity relationship study, a convergent strategy was developed to obtain several pseudosugars from a single synthetic precursor. Furthermore, the glucosylation of streptol was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In addition to kirkamide, other glucosides, such as streptol glucoside, were identified in P . punctata [28,34,66,68]. Streptol glucoside has been shown to inhibit germination of lettuce seeds, which could give the host an allelopathic advantage [66,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to kirkamide, other glucosides, such as streptol glucoside, were identified in P . punctata [28,34,66,68]. Streptol glucoside has been shown to inhibit germination of lettuce seeds, which could give the host an allelopathic advantage [66,68].…”
Section: Discussionmentioning
confidence: 99%
“…punctata [28,34,66,68]. Streptol glucoside has been shown to inhibit germination of lettuce seeds, which could give the host an allelopathic advantage [66,68]. Although we did not investigate functional pathways within our study to support one of these hypotheses, the growth difference in a controlled nutrient-rich environment (and in absence of any herbivores) suggests that benefits of the bacterial leaf nodulation are not solely ameliorating the host’s defence.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling of previously underexplored ecosystems has in turn led to the discovery of novel lipodepsipeptides and darobactin from insect microbiomes (Ganley et al ., 2018; Imai et al ., 2019), lobatamides from a plant symbiont (Ueoka et al ., 2020), or lugdunin from the human gut microbiota (Zipperer et al ., 2016). Inspired by these studies, and our own realization that specialized metabolism forms the basis of several obligate bacterial leaf symbioses (Sieber et al ., 2015; Carlier et al ., 2016; Pinto‐Carbó et al ., 2016, 2018; De Meyer et al ., 2019; Hsiao et al ., 2019), we hypothesized that the above‐ground surfaces of plants could provide rich and underexplored opportunities for the discovery of novel bioactive metabolites. The phyllosphere in particular hosts taxonomically diverse communities and harbours a majority of culturable taxa (Kinkel, 1997; Whipps et al ., 2008; Bai et al ., 2015; Massoni et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that more than 10% of the proteome of Ca . Burkholderia kirkii , the obligate symbiont of Psychotria kirkii , was dedicated to the synthesis of cyclitol compounds with insecticidal an herbicidal properties [69, 70]. Similarly, the leaf nodule symbiont of Ardisia crenata synthesizes FR900359, a depsipeptide inhibitor of mammalian Gq proteins and potent insecticide [10, 14].…”
Section: Discussionmentioning
confidence: 99%